2003
DOI: 10.1128/aac.47.2.809-812.2003
|View full text |Cite
|
Sign up to set email alerts
|

Daily Variations in Ceftriaxone Pharmacokinetics in Rats

Abstract: The aim of this study was to determine whether the time of day ceftriaxone was administered modified its pharmacokinetics. Ceftriaxone was given intraperitoneally at either 0400, 1000, 1600, and 2200 h to Sprague-Dawley rats synchronized under a light-dark cycle of 12 h of light and 12 h of dark. Pharmacokinetic parameters were analyzed for the presence of a 24-h rhythm. Results showed significant daily variations (P < 0.05) in ceftriaxone clearance, with the highest values during the dark phase. It is conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
(19 reference statements)
3
19
0
Order By: Relevance
“…The biliary and renal clearances of ampicillin were significantly higher during the active compared with sleep cycle of rats (White et al, 1995;Mesnard-Ricci and White, 1998). The disposition of ceftriaxone in the rat exhibited significant daily changes attributed mainly to an enhanced excretion during the active period (Rebuelto et al, 2003b). Thus, the finding of a higher clearance of gentamicin during the daytime (08:00 h) in day-active dogs observed in our study is consistent with the greater elimination of other hydrophilic drugs in the active phase of various other species.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The biliary and renal clearances of ampicillin were significantly higher during the active compared with sleep cycle of rats (White et al, 1995;Mesnard-Ricci and White, 1998). The disposition of ceftriaxone in the rat exhibited significant daily changes attributed mainly to an enhanced excretion during the active period (Rebuelto et al, 2003b). Thus, the finding of a higher clearance of gentamicin during the daytime (08:00 h) in day-active dogs observed in our study is consistent with the greater elimination of other hydrophilic drugs in the active phase of various other species.…”
Section: Discussionmentioning
confidence: 95%
“…Chronokinetics is the study of biological rhythmdependent differences in drug absorption and disposition according to the time of day when medications are administered. Several authors have reported temporal variations in the pharmacokinetics of antimicrobial drugs, such as aminoglycosides (Lin et al, 1994;Bleyzac et al, 2000), betalactams (White et al, 1995;Mesnard-Ricci and White, 1998;Rebuelto et al, 2003a), and fluoroquinolones (Sarveshwer Rao et al, 1997;Rebuelto et al, 2003b). Moreover, previous studies on laboratory animals have shown temporal variations in the renal toxicity induced by tobramycin (Lin et al, 1994), isepamicin (Yoshiyama et al, 1993), and gentamicin (Beauchamp et al, 1997) with a peak observed when treatment is administered during the resting period, and a trough when given during the activity period.…”
Section: Introductionmentioning
confidence: 92%
“…In human beings, ciprofloxacin (Sarveshwer Rao et al, 1997) and amikacin (Bleyzac et al, 2000) urinary elimination was greater in the morning than evening. The renal excretion of ampicillin (White et al, 1995), norfloxacin (Rebuelto et al, 2003a), and ceftriaxone (Rebuelto et al, 2003b) was significantly higher during the active compared with the sleep cycle of rats. In dogs administered gentamicin at different times of day, total drug clearance exhibited its minimum during the nighttime (Widerhon et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Two days before treatment inception, a brief startle session was performed to obtain experimental and control groups matched for startle reactivity (matching session; Geyer and Swerdlow, 1998;Martinez et al, 1999). In all experimental groups, PPI test was conducted at day 10 (2 days after CEF withdrawal) to allow complete clearance of the antibiotic (Rebuelto et al, 2003), 30 min after the injection of saline or LY379268.…”
Section: Ppi Of the Startle Reflexmentioning
confidence: 99%